The relationship between conflict management styles and employee’s performance at Kolej Poly-Tech Mara (KPTM) Kota Bharu / Wan Nor Nazirah Wan Kamaruzaman - Wan Kamaruzaman, Wan Nor Nazirah (2014)
Conflict management is an important issue in our daily life The purpose of the study is to identify the effect of the conflicts towards the level of employees performance. If the level of employees' performance is high, it means that the conflict has positive impact towards employee's performance The study is focused on the way employees' handling their conflict and the result are analyzed by descriptive statistics. In other words is to know the employees' conflict management style when they have a conflict. There are four types of conflict, which is intrapersonal conflict, interpersonal conflict, intergroup conflict, and intragroup conflict. While, conflict management styles are divided into five. That is avoiding, competing, accommodating, compromising, and collaborating. In the study, it will show how well the employees handle their conflict and whether it give a positive or negative impacts toward the level of employees performance.